Levels of matrix metalloproteinase-9 and tissue inhibitor of metalloproteinase-1 are related to cardiopulmonary injury in fetal inflammatory response syndrome (Clinics, 2020)
OBJECTIVES: To evaluate the diagnostic value of matrix metalloproteinase-9 (MMP-9), tissue inhibitor of metalloproteinase-1 (TIMP-1), and the MMP-9/TIMP-1 ratio in fetal inflammatory response syndrome (FIRS), and determine a possible association with the incidence of bronchopulmonary dysplasia (BPD) and myocardial injury. METHODS: Overall, 61 cases of preterm infants with FIRS were divided into the FIRS group 1 (p32 weeks) and FIRS group 2 (32 to 37 weeks). Similarly, 57 cases of normal preterm infants were divided into Control group 1 and Control group 2. Levels of interleukin-6 (IL-6), MMP-9, and TIMP-1 were detected by enzyme-linked immunosorbent assay. Spearman’s linear correlation was used to analyze the relationship between dependent variables. Pathological changes were examined by hematoxylin and eosin (HE) staining and in amniotic fluid smears. RESULTS: Levels of IL-6, MMP-9, and TIMP-1, and the MMP-9/TIMP-1 ratio were significantly higher in the FIRS group than in the Control groups. IL-6 was positively correlated with MMP-9, TIMP-1, and the MMP-9/TIMP-1 ratio. Areas under the curve (AUC) of MMP-9, TIMP-1, and the MMP-9/TIMP-1 ratio were 0.92, 0.90, and 0.95, respectively. HE staining and amniotic fluid smears showed the aggregation of inflammatory cells. MMP-9, TIMP-1, and the MMP-9/TIMP-1 ratio were closely related to the incidence of BPD (p32 weeks) and myocardial injury (o37 weeks) in preterm infants. CONCLUSION: MMP-9, TIMP-1, and the MMP-9/TIMP-1 ratio revealed a certain diagnostic value for FIRS; combined with gestational age, these parameters were effective for predicting cardiopulmonary injury.